Comprehensive analysis of peripheral T-cell and natural killer/T-cell lymphoma in Asian patients: A multinational, multicenter, prospective registry study in Asia - Yoon, SE (Elsevier BV, 2021)
10.1016/j.lanwpc.2021.100126